Income distribution and economic crises - Bilin Neyaptı; Derin Akşit (Koç University-TÜSİAD Economic Research Forum (ERF), 2015)
This paper analyzes the relationship between income distribution and the severity of economic crises, where the severity is measured by the length and the depth of the recessions. Using an extensive panel dataset on income distribution and employing an event study framework, we find significant evidence that there is a negative association between the prevailing degree of income inequality and the severity of the recessions. In the case of high income countries that have bad income distribution, however, recessions are observed to be longer than the average. This observation is likely to result from the combination of the strong status-quo bias of the financially powerful income groups and the available means to redistribute towards the poor so as to help mitigate the pressures for reforms to improve income distribution via creative destruction. The longer period of recessions observed in developed countries than in less developed countries in the aftermath of the Great Recession is in support of this argument. The findings also reveal that recessions tend to be longer during the decade of the 1990s than the rest of the period studied. The evidence regarding the corrective effect on the recessions of accommodative fiscal or monetary policy stance, measured by the size of the government and the inflation rate, is observed to be only barely significant on average. Wirh regard to the impact of recessions on income distribution, the evidence in the paper indicates that the post-crises income distribution worsens significantly with the length but improves with the depth of the preceding recession. We also note that, in addition to the persistence effect, the lack of monetary discipline worsens income distribution in the postcrises period significantly.
Keywords: E25; E32; O11; 330; Recession; Income Distribution